Pengaruh Motivasi Kerja, Work Familiy Conflict, Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan (Study Pada Kantor BPBD Kab Lembata. NTT) - Mufidah, Wulandari; Basalamah, Muhammad Ridwan; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to determine the influence of work motivation, work-family conflict, and the work environment on employee productivity. The approach used was a quantitative method, with the primary instrument being a questionnaire administered to all employees of the Lembata Regency Regional Disaster Management Agency (BPBD) as respondents. Data analysis was performed using multiple linear regression to determine the extent of influence of each variable on employee productivity. The results of the analysis Y = 13.981 + 0.560 x1 + -.294 x2 + -.234 x3 + e. From these results it is known that Work Motivation (X1) and Work Family Conflict (X2) have a positive and significant influence on work productivity (Y). However, the Work Environment (X3) does not show a significant influence on employee productivity. This is supported by the results of the partial test (t) on the employee work motivation variable (X1) which has a Sig value of 0.000 <0.05 and a t-count value of 4.805> t-table 2.660, the work family conflict variable (X2) has a sig value of 0.000 <0.05 and a t-count value of -4.045> t-table 2.660 and the employee work environment variable (X3) has a sig value of 0.104> 0.05 and a t-count value of -.1654 <t-table 2.660, also the results of the simultaneous test (f) show a significant 0.000 <0.05 and a calculated f value of 13.948> f table 2.76 the results of the determinant coefficient analysis show 46.6% employee work productivity (Y) is influenced by the variables of work motivation (X1), Work Family Conflict (X2) and Work Environment (X3). The difference of 53.4% is influenced or explained by other variables not included in the study. Keywords: Work Motivation, Work Family Conflict, Work Environment, Employee Work Productivity